DESAIN PEMBELAJARAN KOOPERATIF BERBASIS MACROMEDIA FLASH UNTUK MATA PELAJARAN TEKNOLOGI INFORMASI & KOMUNIKASI - Aminah, Sitti -; -, Syamsurizal -; Harjono, Hary Soedarto (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
This research is aimed at developing a cooperative learning design using Macromedia Flash for Senior High School Level. The design is developed by applying Borg & Gall’s model of Research and Development, which consists of some stages: 1)research information collecting, 2) planning, 3) develop preliminary product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, 10) dissemination and implementation. The result shows that the cooperative learning design mediated by Macromedia Flash is apparently effective to be implemented at the Information and Communcation Technology lesson. Kata kunci: pembelajaran kooperatif, teknologi informasi dan komunikasi